Current bioeconomical interest in stramenopilic Eustigmatophyceae: a review. Issue 1 (1st January 2019) - Stoyneva-Gärtner, Maya; Uzunov, Blagoy; Gärtner, Georg; Borisova, Cvetanka; Draganova, Petya; Radkova, Mariana; Stoykova, Petya; Atanassov, Ivan
Abstract: Today's global problems and challenges have given rise to a new field of interest – bioeconomics . It is strongly related to phycoprospecting, or searching for specific algal strains of commercial importance. There has been growing interest in the small algal class Eustigmatophyceae in recent years. These microscopic stramenopilic algae, which have all the advantages of microalgal cultivation, have proved to be promising commercial sources of valuable compounds (e.g. carotenoids, unsaturated fatty acids, amino acids) in aquaculture, agriculture, biofuels production, medicine, pharmaceutics, cosmetics, wastewater treatment, environmental control, etc. The present review shows the main genera and strains of commercial importance, outlines their main fields of application and some gaps in our knowledge in this aspect. Today, the great promising bioeconomical potential of these algae has generally been recognized, but in the present state of its infancy, it is far from being fully exploited.